A Link Between Communities of Protective Endosymbionts and Parasitoids of the Pea Aphid Revealed in Unmanipulated Agricultural Systems - Leclair, Mélanie; Buchard, Christelle; Mahéo, Frédérique; Simon, Jean-Christophe; Outreman, Yannick (Frontiers in Ecology and Evolution, 2021)
In the last decade, the influence of microbial symbionts on ecological and physiological traits of their hosts has been increasingly recognized. However, most of these effects have been revealed under laboratory conditions, which greatly simplifies the complexity of the factors involved in the dynamics of symbiotic associations in nature. The pea aphid, Acyrthosiphon pisum, forms a complex of plant-adapted biotypes, which strongly differ in the prevalence of their facultative symbionts. Some of the facultative symbionts of A. pisum have been shown to confer protection against natural enemies, among which Hamiltonella defensa is known to protect its host from parasitoid wasps. Here, we tested under natural conditions whether the symbiont communities of different A. pisum biotypes had a protective effect on their hosts and whether symbiont communities and parasitoid communities associated with the pea aphid complex were linked. A space-time monitoring of symbiotic associations, parasitoid pressure and parasitoid communities was carried out in three A. pisum biotypes respectively specialized on Medicago sativa (alfalfa), Pisum sativum (pea) and Trifolium sp. (clover) throughout the whole cropping season. While symbiotic associations, and to a lesser extent, parasitoid communities were stable over time and structured mainly by the A. pisum biotypes, the parasitoid pressure strongly varied during the season and differed among the three biotypes. This suggests a limited influence of parasitoid pressure on the dynamics of facultative symbionts at a seasonal scale. However, we found a positive correlation between the α and β diversities of the symbiont and parasitoid communities, showing some reciprocal interactions. Also, we revealed a negative correlation between the prevalence of Hamiltonella defensa and Fukatsuia symbiotica in co-infection and the intensity of parasitoid pressure in the alfalfa biotype, confirming in field conditions the protective effect of this symbiotic combination.